2012
DOI: 10.1038/ncomms1690
|View full text |Cite
|
Sign up to set email alerts
|

Wide bandgap tunability in complex transition metal oxides by site-specific substitution

Abstract: Fabricating complex transition metal oxides with a tunable bandgap without compromising their intriguing physical properties is a longstanding challenge. Here we examine the layered ferroelectric bismuth titanate and demonstrate that, by site-specific substitution with the mott insulator lanthanum cobaltite, its bandgap can be narrowed by as much as 1 eV, while remaining strongly ferroelectric. We find that when a specific site in the host material is preferentially substituted, a split-off state responsible f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
154
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(163 citation statements)
references
References 34 publications
5
154
0
Order By: Relevance
“…In addition, there has been a renewed interest in the optical properties of ferroelectric BiT as noncentrosymmetric crystal structure of room temperature BiT could trigger asymmetric electron excitation, relaxation, and scattering leading to photovoltaic effect. 20,21 Ferroelectric BiT with layered perovskite structure has a complex crystal structure (with monoclinic B1a1 symmetry) 22 consisting of alternate stacking of fluorite (Bi 2 O 2 ) 2þ and perovskite-like (Bi 2 Ti 3 O 7 ) 2À layers arranged along the crystallographic c-axis. Room temperature lattice parameters are: a ¼ 5.450(1) Å , b ¼ 5.4059(6) Å , and c ¼ 32.832(3) Å .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there has been a renewed interest in the optical properties of ferroelectric BiT as noncentrosymmetric crystal structure of room temperature BiT could trigger asymmetric electron excitation, relaxation, and scattering leading to photovoltaic effect. 20,21 Ferroelectric BiT with layered perovskite structure has a complex crystal structure (with monoclinic B1a1 symmetry) 22 consisting of alternate stacking of fluorite (Bi 2 O 2 ) 2þ and perovskite-like (Bi 2 Ti 3 O 7 ) 2À layers arranged along the crystallographic c-axis. Room temperature lattice parameters are: a ¼ 5.450(1) Å , b ¼ 5.4059(6) Å , and c ¼ 32.832(3) Å .…”
Section: Introductionmentioning
confidence: 99%
“…Here, first-principles density functional calculations would be useful since such study could shed a detailed insight into the origin of optical property, as shown previously for a number of oxides. 20,[27][28][29] Though considerable attention has been paid toward the experimental studies of optical and dielectric properties of BiT, 15,17,19 very few reports provide a microscopic understanding of the optical properties using first-principles calculations. Among the few reports, Cai et al 30 based on the bond orbital theory concluded that the large nonlinear refractive index of ferroelectric BiT is due to virtual electronic excitation from the filled valence band (VB) to the empty cationic d-orbital at short equilibrium bond lengths.…”
Section: Introductionmentioning
confidence: 99%
“…Although both doped BLT samples showed a dramatically decrease in the optical bandgap, the optical bandgap of the undoped BLT samples agreed well with the reported values. The band gap tuning due to the transition from O 2p to transition metal 3d state were suggested in Co doped BLT [19] and similar analogy can be applied to Fe doped BLT. Cobalt atoms are better for the tunability of the optical bandgap in BLT than iron.…”
Section: Resultsmentioning
confidence: 89%
“…On the other hand, the secondary phase did not contribute to the reduction of the optical bandgap. This is because the bandgap tuning could not be realized with a significant amount of cobalt-rich secondary phases from Bruggenman EMA simulation [19], and formed a negligible amount. The amount of secondary phases in Fe-BLT was higher than Co-BLT.…”
Section: Resultsmentioning
confidence: 99%
“…This approach allows to reduce the band gap of the materials without affecting their ferroelectricity [41][42][43]. After transition metal substitutions of perovskite B-site ions, perovskite oxides can generate various semiconducting ferroelectric oxides [44]. Grinberg et al [45,46] reported a ferroelectric solid solution with a very narrow band gap of 1.39 eV.…”
Section: Improvement Of Materials Propertiesmentioning
confidence: 99%